2022
DOI: 10.1371/journal.pntd.0010609
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the gut microbiota of sand fly vectors of zoonotic visceral leishmaniasis (ZVL) in Iran; host-environment interplay shapes diversity

Abstract: The development of Leishmania parasites within sand fly vectors occurs entirely in the insect gut lumen, in the presence of symbiotic and commensal bacteria. The impacts of host species and environment on the gut microbiome are currently poorly understood. We employed MiSeq sequencing of the V3-16S rRNA gene amplicons to characterize and compare the gut microbiota of field-collected populations of Phlebotomus kandelakii, P. perfiliewi, P. alexandri, and P. major, the primary or secondary vectors of zoonotic vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…Another species collected in the current study was Ph. major , which was reported from 17 out of 31 provinces of Iran with human cases of ZVL and according to the current study, this species was mostly collected from mountainous areas ( 32 , 45 ). Previous morphological and morphometric study in the northwest of the country, showed other morphotypes including Ph.…”
Section: Discussionsupporting
confidence: 62%
“…Another species collected in the current study was Ph. major , which was reported from 17 out of 31 provinces of Iran with human cases of ZVL and according to the current study, this species was mostly collected from mountainous areas ( 32 , 45 ). Previous morphological and morphometric study in the northwest of the country, showed other morphotypes including Ph.…”
Section: Discussionsupporting
confidence: 62%
“…Various evolutionary processes in the insect body have led to different types of symbiotic relationships, from free living to an obligate or facultative symbiosis ( Gupta and Nair, 2020 ). There is insufficient information on the type of symbiosis between B. subtilis and E. cloacae together and with the host insect, but evidence of their co-occurrence in the gut of eight sand fly species ( Maleki-Ravasan et al., 2015 ; Karimian et al., 2019 ; Karimian et al., 2022 ) and their transmission while biting ( Maleki-Ravasan, in press ) have been provided. While these two bacteria were pre-coexisted in sand fly gut, in the present study, they first were isolated, then sub-cultured separately and finally combined while injecting into the mice, which resulted in relatively severe symptoms of L. major , though it may not be the case in natural settings.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of bacteria including the members of Enterobacter cloacae and Bacillus subtilis complexes are commensal bacteria in the gut of sand flies that transmit causative agents of CL and VL in the Old and New Worlds ( Oliveira et al., 2000 ; Hurwitz et al., 2011 ; Akhoundi et al., 2012 ; Maleki-Ravasan et al., 2015 ; Fraihi et al., 2017 ; Gunathilaka et al., 2020 ; Karimian et al., 2022 ). Both bacteria have the ability to regulate insect immune responses ( Eappen et al., 2013 ; Heerman et al., 2015 ; Zhang et al., 2021 ) and produce secondary metabolites that show activity against insects and their harboring microorganisms ( Eappen et al., 2013 ; Caulier et al., 2019 ; Zhang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Screening was followed by using other loci: ftsZ , fbpA , gatB , CoxA , gltA , GroEL , 16s rRNA , and dnaA , using the primers and thermal program shown in Tables 1 and 2 . Control DNA samples were prepared using double distilled water (ddH 2 O) as negative and previously confirmed adult females of either the Culex pipens mosquito [ 48 ] or the Phlebotomus papatasi sand fly [ 43 ] as positive controls, infected respectively with the w Pip or w Pap strains of Wolbachia . PCR amplifications were performed in an automatic thermocycler (Eppendorf, Germany) in a total volume of 25 μl containing 2–5 μl (~0.5 μg) of genomic DNA, 12.5 μL of Taq DNA Polymerase 2x Master Mix RED, Ampliqon (Denmark), 1 μL of each primer (10 mM), supplemented with ddH 2 O. PCR products were electrophoresed on 1% agarose gels with a voltage of 85 v and time less than 30 minutes, and the size of each PCR product was estimated using a 100-base pair (bp) molecular marker (SinaClon, Iran), visualized under a UV transilluminator.…”
Section: Methodsmentioning
confidence: 99%